Interaction of Garlic with Carvedilol during Ischemia-Reperfusion Induced Myocardial Damage in Rats: Pharmaceutical Science-Pharmacology for drug discovery - Syed Mohammed Basheeruddin Asdaq; Yahya Ali Mohzari (International Journal of Life Science and Pharma Research, 2022)
Concurrent administration of herbs with drugs may magnify, oppose or mimic the pharmacological effect of each other. The current research was carried out to determine the cardio protective potential of garlic homogenate (GH) when administered with carvedilol (CAR) on ischemia-reperfusion injury (IRI) in isolated rat heart preparation. Pretreated male albino rats were anesthetized, hearts were excised and mounted on modified Langendorff setup, perfused with physiological salt solution, after initial stabilization, subjected to 15 min global no flow ischemia (IRI) and re-perfused. Prior treatment of animals with CAR, GH-125 and GH-250 showed significant recovery from IRI induced myocardial damage evident from significant decline in LDH and CK-MB in post-ischemic perfusate; this was further validated by incline in the above biomarkers in the heart tissue homogenate (HTH). Further, significant recovery of developed tension and heart rate were found in treated groups when compared to control. Furthermore, GH-250 treated groups with CAR showed significant increase in endogenous antioxidant enzyme like SOD and catalase activities. This enhanced antioxidant activities might be due to possible role of CAR in augmenting the role of GH to either increase synthesis of antioxidants or trigger degeneration of oxidants. However, high dose of GH-500 failed to provide similar results in presence of CAR. In conclusion, simultaneous administration of CAR and moderate dose of GH (250 mg/kg) provided enhanced protection to myocardium from myocardial injury when compared to their individual administration. Therefore, diet containing moderate quantities of garlic could prove beneficial to the heart and administration of garlic with CAR produces additive effect.